Educational Leadership: The Buddhist Perspective - บูรณะกิติ, สะริญญาลภัสธร์ (Journal of Educational Review Faculty of Education in MCU, 2018)
Educational leader is the one who determines the direction of a particular organization. In Buddhism, the educational leader must be good minded, good at knowledge, full of ability and virtue in directing the educational direction. Educational Leadership in the present days needs Buddhist principles to it complete.